Sa se rationalizeze:
![\frac{1}{ \sqrt[4]{7}- \sqrt[4]{3} } \frac{1}{ \sqrt[4]{7}- \sqrt[4]{3} }](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B+%5Csqrt%5B4%5D%7B7%7D-+%5Csqrt%5B4%5D%7B3%7D++%7D+)
![\frac{1}{ \sqrt[6]{2}-1 } = \frac{1}{ \sqrt[6]{2}-1 } =](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B+%5Csqrt%5B6%5D%7B2%7D-1+%7D+%3D)
Răspunsuri la întrebare
Răspuns de
2
ex.1 = (⁴√7 + ⁴√3) / ( ⁴√7 -⁴ √3) ·(⁴√7 + ⁴√3) = ( ⁴√7 + ⁴√3) / ( √7 - √3)
↓
⁴√7² - ⁴√3² = √7 - √3
= (⁴ √7 + ⁴ √3 ) ·(√7 + √3) / ( √7 -√3) · (√7 + √3)
↓
√7² - √3² = 7 -3 = 4
= (⁴√7 + ⁴√3) · (√7 + √3) / 4
ex2.= (⁶ √2² + ⁶√2 + 1) / ( ⁶√2 -1) · (⁶√2² + ⁶√2 +1) =
= a³ - b³
= ⁶√2³ - 1³ = √2 - 1
= (⁶√4 + ⁶√2 + 1 ) / (√2 -1) =
= ( ⁶√4 + ⁶√2 +1 )· (√2 +1) / ( √2 -1) · (√2 +1 ) =
↓
√2² - 1 = 2 -1 =1
= (⁶√4 + ⁶√2 +1) · (√2 +1)
a⁵ + b⁵ = ( a +b) ( a⁴ -a³b+a²b² -ab³ + b⁴ )
ex.3 = (⁵√3⁴ - ⁵√3³ · ⁵√2 + ⁵√3² · ⁵√2² - ⁵√3 · ⁵√2³ + ⁵√2⁴ ) / ( 3 +2 )
= ( ⁵√81 - ⁵√54 + ⁵√36 - ⁵√24 + ⁵√16 ) / 5
↓
⁴√7² - ⁴√3² = √7 - √3
= (⁴ √7 + ⁴ √3 ) ·(√7 + √3) / ( √7 -√3) · (√7 + √3)
↓
√7² - √3² = 7 -3 = 4
= (⁴√7 + ⁴√3) · (√7 + √3) / 4
ex2.= (⁶ √2² + ⁶√2 + 1) / ( ⁶√2 -1) · (⁶√2² + ⁶√2 +1) =
= a³ - b³
= ⁶√2³ - 1³ = √2 - 1
= (⁶√4 + ⁶√2 + 1 ) / (√2 -1) =
= ( ⁶√4 + ⁶√2 +1 )· (√2 +1) / ( √2 -1) · (√2 +1 ) =
↓
√2² - 1 = 2 -1 =1
= (⁶√4 + ⁶√2 +1) · (√2 +1)
a⁵ + b⁵ = ( a +b) ( a⁴ -a³b+a²b² -ab³ + b⁴ )
ex.3 = (⁵√3⁴ - ⁵√3³ · ⁵√2 + ⁵√3² · ⁵√2² - ⁵√3 · ⁵√2³ + ⁵√2⁴ ) / ( 3 +2 )
= ( ⁵√81 - ⁵√54 + ⁵√36 - ⁵√24 + ⁵√16 ) / 5
Alte întrebări interesante
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Franceza,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Limba română,
10 ani în urmă